The curious out-of-plane conductivity of PEDOT:PSS - Ruit, Kevin van de; Katsouras, Ilias; Bollen, Dirk; Mol, Antonius Maria Bernardus van; Janssen, René A. J.; Leeuw, Dago M. de; Kemerink, Martijn (Advanced functional materials, 2013)
For its application as transparent conductor in light-emitting diodes and photovoltaic cells, both the in-plane and out-of-plane conductivity of PEDOT:PSS are important. However, studies into the conductivity of PEDOT:PSS rarely address the out-of-plane conductivity and those that do, report widely varying results. Here a systematic study of the out-of-plane charge transport in thin films of PEDOT:PSS with varying PSS content is presented. To this end, the PEDOT:PSS is enclosed in small interconnects between metallic contacts. An unexpected, but strong dependence of the conductivity on interconnect diameter is observed for PEDOT:PSS formulations without high boiling solvent. The change in conductivity correlates with a diameter dependent change in PEDOT:PSS layer thickness. It is suggested that the order of magnitude variation in out-of-plane conductivity with only a 3-4-fold layer thickness variation can quantitatively be explained on basis of a percolating cluster model.